Everyday life after a hip fracture: what community-living older adults perceive as most beneficial for their recovery. (26th February 2019) - Pol, Margriet; Peek, Sebastiaan; van Nes, Fenna; van Hartingsveldt, Margo; Buurman, Bianca; Kröse, Ben
Abstract: Objective: to gain insight into what older adults after hip fracture perceive as most beneficial to their recovery to everyday life. Design: qualitative research approach. Setting: six skilled nursing facilities. Participants: 19 older community dwelling older adults (aged 65–94), who had recently received geriatric rehabilitation after hip fracture. Methods: semi-structured interviews were conducted with 19 older adults after hip fracture. Coding techniques based on constructivist grounded theory were applied. Results: four categories were derived from the data: 'restrictions for everyday life', 'recovery process', 'resources for recovery' and 'performing everyday activities'. Physical and psychological restrictions are consequences of hip fracture that older adults have struggled to address during recovery. Three different resources were found to be beneficial for recovery; 'supporting and coaching', 'myself' and 'technological support'. These resources influenced the recovery process. Having successful experiences during recovery led to doing everyday activities in the same manner as before; unsuccessful experiences led to ceasing certain activities altogether. Conclusion: participants highlight their own role ('myself') as essential for recovery. Additionally, coaching provides emotional support, which boosts self-confidence in performing everyday activities. Furthermore, technology can encourage older adults to become more active and being engaged in the recovery process. The findings suggest that more attention should be paid to follow-up interventions after discharge from inpatient rehabilitation to support older adults in finding new routines in their everyday activities. A conceptual model is presented and provides an understanding of the participants' experiences and perspectives concerning their process of recovery after hip fracture to everyday life.